Molecularly Imprinted Polymers: Compromise between Flexibility and Rigidity for Improving Capture of Template Analogues. Issue 12 (24th February 2014) - Pardo , Antonelle; Mespouille, Laetitia; Dubois, Philippe; Blankert, Bertrand; Duez, Pierre
Abstract New synthetic strategies for molecularly imprinted polymers (MIPs) were developed to mimic the flexibility and mobility exhibited by receptor/enzyme binding pockets. The MIPs were prepared by bulk polymerization with quercetin as template molecule, acrylamide as functional monomer, ethylene glycol dimethacrylate as cross‐linker, and THF as porogen. The innovative grafting of specific oligoethylene glycol units onto the imprinted cavities allowed MIPs to be obtained that exhibit extended selectivity towards template analogues. This synthetic strategy gives promising perspectives for the design of molecular recognition of molecules based on a congruent pharmacophore, which should be of interest for drug development.